Incidence of metastasis in circumflex iliac nodes distal to the external iliac nodes in cervical cancer - Takeshita, Sho (J Gynecol Oncol, 2016)
OBJECTIVE: A causal relationship between removal of circumflex iliac nodes distal to the external iliac nodes (CINDEIN) and lower leg edema has been recently suggested. The aim of this study was to elucidate the incidence of CINDEIN metastasis in cervical cancer. METHODS: A retrospective chart review was carried out for 531 patients with cervical cancer who underwent lymph node dissection between 1993 and 2014. CINDEIN metastasis was pathologically identified by microscopic investigation. After 2007, sentinel lymph node biopsy was performed selectively in patients with non-bulky cervical cancer. The sentinel node was identified using (99m)Tc-phytate and by scanning the pelvic cavity with a γ probe. RESULTS: Two hundred and ninety-seven patients (55.9%) underwent CINDEIN dissection and 234 (44.1%) did not. The percentage of International Federation of Gynecology and Obstetrics stage IIb to IV (42.4% vs. 23.5%, p<0.001) was significantly higher in patients who underwent CINDEIN dissection than those who did not. CINDEIN metastasis was identified in 1.9% overall and in 3.4% of patients who underwent CINDEIN dissection. For patients with stage Ia to IIa disease, CINDEIN metastasis was identified in 0.6% overall and in 1.2% of patients who underwent CINDEIN dissection. Of 115 patients with sentinel node mapping, only one (0.9%) had CINDEIN detected as a sentinel node. In this case, the other three lymph nodes were concurrently detected as sentinel lymph nodes. CONCLUSION: CINDEIN dissection can be eliminated in patients with stage Ia to IIa disease. CINDEIN might not be regional lymph nodes in cervical cancer.